Trocas gasosas, composição mineral, produção e qualidade de maracujazeiro amarelo irrigado com água salina e adubado com potássio e biofertilizante - Nunes, Járisson Cavalcante (2016)
The yellow passion fruit cultivation provides elevated social and economic importance to all regions of Brazil. In this sense, an experiment was conducted from May 2013 to December 2014, in the municipality of Remígio – PB, to evaluate the effects of irrigation with saline water, biofertilizer and potassium in the soil chemical attributes, mineral composition, gas exchanges, production and yellow passion fruits quality. The treatments were disposed on randomized blocks with subdivided plots, using factorial scheme 2 x 3 x 5, related to two electrical conductivity levels of irrigation water in the major plot (0.35 and 4.00 dS m-1), and the combination of three potassium sources (without fertilization, fertilized with slow liberation and conventional potassium chloride) in the sub-plot and five dosages of biofertilizer (0, 25, 50, 75 and 100% of the dosages 15 L m-2), with three replicates and four plants per plot. To evaluation of the pH, electrical conductivity of the saturation extract, stomatal conductance, transpiration, liquid photosynthesis, carbon internal concentration and production compounds, as well as factorial cited above, we inserted two evaluation periods (sub-plot). To process data we used the statistical software SAS®. The interaction water × potassium × biofertilizer provided significant effects in the levels of organic matter, phosphorus, potassium, sodium, potential acidity, bases saturation, electrical conductivity of the saturation extract and percentage of exchangeable sodium in the superficial soil layer, and in the levels of organic matter, sodium, potential acidity, bases saturation, and electrical conductivity of the saturation extract in the depth 21-40 cm. The same interaction interfered significantly in the foliar levels of phosphorus, potassium, calcium, boron, copper, manganese, zinc and sodium, and in the fruit quality compounds referent to fruit longitudinal and transversal diameter, firmness, pulp yield and titratable acidity. Biofertilizer increased organic matter, phosphorus and potassium levels in the superficial and sub-superficial layers, regardless of the source of potassium used and the electric conductivity of irrigation water. Potassium chloride coatedwith organic polymers increased the pH values in layer 0-20 cm and phosphorus and calcium values in depth 21-40 cm in the treatments irrigated with non-saline water. The irrigation in the dry season increased the soil character from non-saline to saline. The waters from the rainy season leach part of the salt added by the irrigation water. At the beginning of flowering, passion fruit plants „BRS Gigante Amarelo‟ were adequately supplied in N, P and K, and deficient in calcium, magnesium, boron, iron, copper, manganese and zinc. The salinity of irrigation water decreased the stomatal conductance, the transpiration and liquid photosynthesis, and in the treatments with potassium chloride coatedwith polymers increased internal concentration of carbon. The biofertilizer associated to potassium fertilization increased the yellow passion fruit production compounds. The levels of soluble solids, titratable acidity, pulp yield and fruit vitamin C were adequate to the consume patterns required by the market.